Analisis Pendapatan Usahatani Padi Sawah Di Desa Mogoyunggung Dua Kecamatan Dumoga Timur Kabupaten Bolaang Mongondow - Kawengian, Gerandi S.; Kapantow, Gene Henfried Meyer; Baroleh, Jenny (Sam Ratulangi University, 2023)
This study aims to determine the amount of farmers income in paddy rice in Mogoyunggung Dua Village, Dumoga District East Bolaang Mongondow Regency. Thris research was conducted for 3 months, namely from Oktober to Desember 2022, which is located in Mogoyunggung Dua Village. The Population collection in this study used a census technique for lowland rice farmers. As for the determination of the sample that is with took 19 people incolved in paddy rice farming. The results of the study show that the average income of paddy rice farming obrained by farmers in Mogoyunggung Dua Village is IDR465.990.000 while the average per ha is IDR13.645.000. Farming costs are all expenses that occur during a certain period of time. The average cost of lowland rice farming incurred by farmers in Mogoyunggung Dua Village is IDR189.529.671 while the average bus pm ha is IDR5.549.917.